The impact of pilot policies for low carbon city construction on the development of urban circular economy multiple time-point difference-in-differences model - Xiao, Shumei; Liu, Yulan; Rong, Jing; Wang, Wei (Frontiers in Environmental Science, 2024)
As a means of environmental regulation, the low-carbon city pilot policy aims to deal with climate change and alleviate the pressure on environmental resources in economic development. This paper studies the impact of low-carbon city pilot policies on the development of urban circular economy to provide a reference for policy formulation. Based on the panel data of 273 prefecture-level cities from 2012 to 2022, the paper constructs an evaluation index system for urban circular economy development. It integrates the analytic hierarchy process (AHP) and entropy method for comprehensive evaluation. By taking pilot policies of low-carbon cities as quasi-natural experiments, the multiple time-point difference-in-differences model is used to evaluate the impact of policies. The intermediary effect model is used to test the mechanism of each factor in the development of the urban circular economy. The results demonstrated that at the significance level of 1%, the coefficient of explanatory variables was significant, and the development level of the urban circular economy was significantly increased by 6.3% after adding control variables. The construction of low-carbon pilot cities has improved the development performance of the circular economy by about 6.42%. The intermediary effect of industrial structure rationalization was significantly positive at the 1% significance level, indicating that the construction of low-carbon pilot cities has dramatically promoted the coordinated development of intra-industry relations in the region. The paper shows that the low-carbon city pilot policy has a significant role in promoting the development of the urban circular economy. Therefore, it is suggested to further expand the scope of low-carbon city pilot to give full play to its promoting effect.